Does Soybean in Indonesia Still Competitive?: A Policy Analysis Matrix Approach - Febrian Ananta Kahar; Isti Fadah; Edy Wahyudi; Adhitya Wardhono (Universitas Negeri Malang, 2023)
The low productivity of soybeans in Indonesia is one of the reasons why domestic production cannot meet market demand. In addition to suboptimal and contradictory government policies, they contribute to domestic soybean competitiveness against imported soybeans. The purpose of this study is to analyze the economic and financial profitability of farming, analyze the competitiveness status of soybeans, analyze the impact of government policies on soybean competitiveness, and analyze the sensitivity of domestic soybean competitiveness. This study applies the Policy Analysis Matrix (PAM). The results of this analysis are used to observe two basic indicators to measure competitiveness and assess the role of government policies. This research uses a case study of soybean farmers in the Jember Regency area. The analysis results show that the soybean farming business in Jember Regency is capable of generating economic profits. Soybean farming in Jember is capable of producing comparative and competitive advantages. Furthermore, the policy analysis reveals that the impact of the soybean policy on farming in the region is not yet optimal. Therefore, new governance policies are needed. Parameter analysis in the PAM analysis indicates that price and productivity variables have a potential role in increasing production and domestic soybean competitiveness.